Linguistic Complexity: Relationships Between Phoneme Inventory Size, Syllable Complexity, Word and Clause Length, and Population Size - Fenk-Oczlon, Gertraud; Pilz, Jürgen (Frontiers in Communication, 2021)
Starting from a view on language as a complex, hierarchically organized system composed of many parts that have many interactions, this paper investigates statistical relationships between the linguistic variables ‘phoneme inventory size’, ‘syllable complexity’, ‘length of words’, ‘length of clauses’, and the nonlinguistic variable ‘population size’. By analyzing parallel textual material of 61 languages (18 language families) we found strong positive correlations between phoneme inventory size and mean syllable complexity (measured as number of phonemes) and between phoneme inventory size and mean number of monosyllabic words. We observed significant negative correlations between phoneme inventory size and the mean length of words and the mean length of clauses, measured as number of syllables. We then correlated the linguistic complexity data with estimated speaker population sizes and could reveal that languages with more speakers tend to have * more phonemes per syllable, * shorter words in number of syllables, * a higher number of monosyllabic words, * and a higher number of words per clause. Moreover, we reproduce the results of former studies that found a positive correlation between population size and phoneme inventory size for our language sample. The findings are discussed in light of previous research and within the framework of Systemic Typology. We propose that syllable complexity is a key factor in the correlations identified in this study, and that Zipf’s law of Abbreviation explains the associations between ‘word length’, ‘phoneme inventory size’ and the extralinguistic variable ‘population size’.